Ensuring the quality of the educational process at higher education institutions in serbia with special reference to the importance of students in the self-evaluation process - Velida Zimonjić (Economic Themes, 2024)
Aware of the fact that they can ensure their survival on the educational scene only if they follow modern trends and requirements that come from today's highly changed and turbulent educational environment, national bodies that are in charge of defining educational policies, quality assurance systems and their successful implementation and control, together with universities in Serbia are trying to respond to the challenges they face in the best possible way, and use them as an opportunity to improve the quality of education and acquire competitive advantages. The implementation of the quality system, continuous improvement and upgrading of the quality in all aspects of work of higher education institutions has become a necessity, in view of the fact that education process is a service, the quality of which is assessed both by national bodies in charge of accreditation and the evaluation of achieved results, and by students. When a suitable climate and culture is created to promote quality as a common goal of all participants involved in the educational process, and when the focus is on the quality of the teaching process, scientific and research work, administration, equipment, ambience, i.e. the environment where the educational service process takes place, only then can we expect the learning outcomes to achieve outstanding results to the satisfaction of the students. One of the elements of the quality assessment, as an integral part of the accreditation process is the self-evaluation report, which includes the presentation of the achieved results and the degree of fulfilment of the defined standards. In the process of self-evaluation, a special place and importance belongs to students, therefore, this paper will pay special attention to the Standard 13, which refers to the involvement of students in the process of self-evaluation of higher education institutions in Serbia.
Keywords: M30; I23; 330; quality; higher education institutions; universities; quality improvement systems; National Accreditation Body; students; self-evaluation